2007
DOI: 10.1002/ajmg.b.30501
|View full text |Cite
|
Sign up to set email alerts
|

Low brain‐derived neurotrophic factor (BDNF) levels in serum of Huntington's disease patients

Abstract: Huntington's disease (HD) is a neurodegenerative disorder characterized by motor, cognitive, and psychiatric symptoms and by a progressive degeneration of neurons in basal ganglia and in brain cortex. Brain-derived neurotrophic factor (BDNF) is a pro-survival factor for striatal neurons. Some evidence implicates a brain BDNF deficiency, related to mutated huntingtin expression, in the selective vulnerability of striatal neurons in HD. We compared BDNF serum levels in 42 patients with HD (range 28-72 years, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 31 publications
9
91
1
Order By: Relevance
“…This delayed increase coincides with significant improvements in memory and learning achieved after longitudinal intervention. Our results are in accord with previous evidence demonstrating reduced BDNF/BDNF levels in Huntington's disease, in both humans and animal models [95][96][97][98][99][100] , and activity-dependent increases in BDNF expression in animals 77,82,104,105,109,110 and in human populations [106][107][108] . During the course of this investigation, however, a recent publication has questioned the utility of BDNF measurement as a biomarker for the monitoring of Huntington's disease 162 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This delayed increase coincides with significant improvements in memory and learning achieved after longitudinal intervention. Our results are in accord with previous evidence demonstrating reduced BDNF/BDNF levels in Huntington's disease, in both humans and animal models [95][96][97][98][99][100] , and activity-dependent increases in BDNF expression in animals 77,82,104,105,109,110 and in human populations [106][107][108] . During the course of this investigation, however, a recent publication has questioned the utility of BDNF measurement as a biomarker for the monitoring of Huntington's disease 162 .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports [95][96][97][98][99][100][101] , the ELISA results indicated lower levels of BDNF in the whole blood of Huntington's disease individuals, relative to normative data ( Figure 26). The assay to detect changes in mean BDNF concentration over the time period of the study revealed a non-significant reduction in mean BDNF levels after the control period (p=0.838) which worsened after one round of intervention (p=0.393).…”
Section: Bdnfsupporting
confidence: 91%
See 2 more Smart Citations
“…In most cases the overwhelming mass of the peripheral tissues inevitably dwarfs the contribution of substances that are released from dying neurons and can penetrate the blood-brain barrier, especially given the very slow rate of CNS cell death in HD. Even seemingly 'CNS-specific' entities that can be detected in peripheral blood, such as brain-derived neurotrophic factor (BDNF) [17], may have peripheral sources that confound their interpretation [18].…”
Section: Introductionmentioning
confidence: 99%